PRAWO I ETYKA W MEDYCYNIEHow knowledgeable are patients about the possibility of refusal to perform a medical procedure on the part of a doctor? - Wroński, Konrad; Bocian, Roman (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Introduction : In the present century both the doctor and the patient have their rights and duties. One of the doctors’ rights is a right to refuse to perform a medical procedure. Aim : The objective of this research was to find out patients’ knowledge of the possibility of a doctor’s refusal to perform a medical procedure. Material and methods : A group of 400 patients treated in Doctor Pirogow’s High Specialized Hospital in Lodz was interviewed by means of the author’s own survey in which specific tools were used to determine patients’ knowledge of the possibility of a doctor’s refusal to perform a medical procedure. The necessary statistics were conducted by means of STATISTICA 7.1 and EXCEL 2008 programs. Results: The analysis of the results shows that 377 (94.25%) respondents were not familiar with the fact that the doctor may refuse to carry out a medical procedure. Among 400 respondents, 23 (5.75%) were informed about this regulation. Conclusions : The results of the research prove that patients are not familiar with the doctors’ right to refuse a medical procedure. A doctor who refuses to perform a medical procedure on a patient should record this fact in hospital documents and also inform the patient about another medical institution were she/he will be able to start or continue treatment.